Protection of Cryptocurrency Investor Asset Security on Indonesian Exchange - Siti Ngaisah (PT Publikasiku Academic Solution, 2023)
Progress in this digital era and the growing economic activity that occurs in human existence, this is also what can be the focus. Due to the widespread use of the internet and social media in the country, the growth of the digital economy in Indonesia is considered to have great potential. In an economic context in this digital era, this is evidence that growth and development are growing. As a result, more and more commerce and commercial transactions use the Internet as a digital medium for communication, collaboration, and joint ventures between individuals or businesses. Cryptocurrencies are one of those things that are now making it easier for people to make virtual commercial transactions. Cryptocurrency is a technique that uses a cryptographic technology system to assist in processing cryptocurrencies, and digital assets. The Greek words graphein, meaning writing or science, and kriptó, meaning hidden or secret, are the sources of the words cryptology and cryptography. In this case, to be able to find out the regulations regarding the legitimacy of using crypto assets in the form of bitcoin to be used as a transaction tool in paying attention to the regulations of the Currency Law, ITE Law, and Bank Indonesia Regulations. As well as to identify whether the losses incurred on crypto assets can be guaranteed for their civil rights